REKRUTMEN CALON ANGGOTA LEGISLATIF DPR RI DI PARTAI NASDEM PADA PEMILU 2024 - Dandi Alexander (2024)
In a democratic country, political parties have the function of political recruitment. Since the beginning of the reform era, new political parties have emerged, one of which is the NasDem Party. Like other parties in Indonesia, the NasDem Party also performs its function of political recruitment. Political parties in Indonesia, including the NasDem Party, face various problems in their recruitment processes, such as political nepotism, transactional politics, elitism in the recruitment process, and others. Therefore, this research aims to understand how the recruitment process is carried out by the NasDem Party in the 2024 elections. The study uses the theory of political party institutionalization proposed by Vicky Randall and Lars Svasand as its analytical framework to determine how the recruitment process has been conducted by the NasDem Party in the 2024 elections. Data were obtained from interviews and literature reviews. The results of this research indicate that the NasDem Party has not been very effective in its recruitment process. This is evidenced by the fact that the NasDem Party only institutionalizes in one dimension according to Randall and Svasand's theory of political party institutionalization, specifically in the degree of systematization. In the other three dimensions-value identity, decisional autonomy, and reification-the NasDem Party has not yet institutionalized. This study recommends that the NasDem Party reevaluate its recruitment process to avoid similar issues in future recruitment processes.